2011
DOI: 10.1111/j.1533-2500.2011.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

High Doses of Topical Amitriptyline in Neuropathic Pain: Two Cases and Literature Review

Abstract: Severe chronic neuropathic pain is a challenge to treat, and due to adverse effects of classical oral medication, optimal and effective dose levels are difficult to reach. Therefore, administration of topical analgesics might be an option, due to reduced adverse effects, and increased patient compliance. The aim of this article is to describe two cases treated effectively with topical amitriptyline 5% and 10%, the highest dosage described to date. The first patient was a 39-year-old man, suffering from severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 51 publications
1
57
0
Order By: Relevance
“…If one considers the picture emerged from a more precise dissection of the nociceptive circuitries in the substantia gelatinosa of the spinal cord (Figure2), amitriptyline has the potential to target at the same time a pro-(BDNF) and an antinociceptive (GDNF) factor at this very important relay station. Notably, a very recent study has shown that systemic (intraperitoneal) amitriptyline reversed the effects of allodynia and hyperalgesia induced by chronic constriction injury (CCI) in mice [93], and case reports in the clinical literature indicate that high doses of topical amitriptyline are beneficial in the treatment of neuropathic pain although systemic adverse effects should be taken into account [94] .…”
Section: An Interesting Option For Developing New Drugs Is Thus Targementioning
confidence: 99%
“…If one considers the picture emerged from a more precise dissection of the nociceptive circuitries in the substantia gelatinosa of the spinal cord (Figure2), amitriptyline has the potential to target at the same time a pro-(BDNF) and an antinociceptive (GDNF) factor at this very important relay station. Notably, a very recent study has shown that systemic (intraperitoneal) amitriptyline reversed the effects of allodynia and hyperalgesia induced by chronic constriction injury (CCI) in mice [93], and case reports in the clinical literature indicate that high doses of topical amitriptyline are beneficial in the treatment of neuropathic pain although systemic adverse effects should be taken into account [94] .…”
Section: An Interesting Option For Developing New Drugs Is Thus Targementioning
confidence: 99%
“…In the period 2008-2011 we started compounding a number of creams based on amitriptyline and ketamine and found out that most of the approaches at that time selected a dose too low, based on only 1% to 5%. We found that such analgesics needed to be compounded in creams containing at least 5% and preferably 10% of the active ingredient [7]. The same holds true for phenytoin, where we also prefer a 10% compounded cream [8].…”
Section: Introductionmentioning
confidence: 93%
“…[137] Although not effective in every trial [138], amitriptyline at concentrations between 2-10%, along with some other antidepressant agents has been successfully used as a topical agent in a number of neuropathic pain states including complex regional pain syndrome (CRPS), multiple sclerosis and vulvodynia. [139][140][141] Amitriptyline has been employed as a sole agent or in combination with other topical agents such as ketamine and baclofen. [142][143][144][145][146][147] Although the topical application of antidepressant drugs can reduce their unwanted central side effects, this form of administration can occasionally lead to adverse toxicity.…”
Section: Facit Ad Maximos Dolores -Useful For Extreme Painmentioning
confidence: 99%